2016
DOI: 10.3390/nu8080493
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Continuing Folic Acid Supplementation after the First Trimester of Pregnancy Increased the Risk of Large-for-Gestational-Age Birth: A Population-Based Birth Cohort Study

Abstract: Supplementation with folic acid (FA) was proven to prevent neural tube defects (NTDs) and was recommended worldwide before and during early pregnancy. However, much less is known regarding the role of FA after the 12th gestational week (GW). This study aimed to investigate the related effects of continued FA supplementation after the first trimester of pregnancy on fetal growth. The study subjects came from the Ma’anshan-Anhui Birth Cohort Study (MABC) that recruited 3474 pregnant women from the city of Ma’ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 29 publications
3
36
0
3
Order By: Relevance
“…The majority of studies demonstrated that supplement use before and during pregnancy reduced the risk of SGA [31,36,38,40,42,44,79]. However, others demonstrated an opposite [39,41] or null effect [30,45]. Thus, further research should be encouraged to understand the effect of folic acid supplement use on the risk of SGA and associated outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies demonstrated that supplement use before and during pregnancy reduced the risk of SGA [31,36,38,40,42,44,79]. However, others demonstrated an opposite [39,41] or null effect [30,45]. Thus, further research should be encouraged to understand the effect of folic acid supplement use on the risk of SGA and associated outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that folate deficiency leads to PTB [27] and SGA [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], but further studies are necessary to better investigate the potential protective role of adequate folate intake and/or folic acid supplementation. To fill this gap, the primary aim of the current study was to describe the prevalence of dietary folate intake and its determinants among pregnant women from Catania (Italy).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown Hcy levels to be positively correlated with the severity of depression [ 12 , 13 , 14 , 15 , 16 ]. Meanwhile, pregnant women require more intake of folate/FA compared to non-pregnant women, and there is a high prevalence of inadequate folate/FA intake among pregnant women [ 11 , 17 ]. According to the mechanism of folate on depression, inadequate folate/FA intake during pregnancy may lead to PPD [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies investigate the relationship between dietary vitamin intake and SGA risk and they report contradictory results. In general, this relationship is addressed through the consumption of multivitamin/mineral supplements [ 16 , 17 , 18 , 19 , 20 ]. Moreover, most have been conducted in low- and middle-income countries [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%